Genomic and tumour microenvironmental biomarkers of immune checkpoint inhibitor response in advanced Taiwanese melanoma - John Wen‐Cheng Chang; Chien‐Jung Huang; Wen‐Kuan Huang; Yu‐Chao Wang; Jia‐Juan Hsieh; Yao‐Yu Chang; Yen‐Lin Huang; Chia‐Ling Wu; Yeh‐Han Wang; Shu‐Jen Chen; Kien Thiam Tan; Chiao‐Ping Chen; et al. (Clinical & Translational Immunology, 2023)
Abstract Objective Genomic biomarkers predicting immune checkpoint inhibitor (ICI) treatment outcomes for Asian metastatic melanoma have been rarely reported. This study presents data on next‐generation sequencing (NGS) and tumour microenvironment biomarkers in 33 cases. Methods Thirty‐three patients with advanced melanoma, who underwent ICI treatment at the Chang Gung Memorial Hospital in Taiwan, were recruited. The study evaluated clinical outcomes, including response rate, disease control rate, progression‐free survival (PFS) rate and overall survival (OS) rate. Archived tissue samples from 33 cases were subjected to NGS by ACTOnco, and ACTTME was employed in 25 cases. Results The most prevalent driver mutations were BRAF mutations (24.2%), followed by NRAS (15.2%), KIT (12.1%), KRAS (9.1%) and NF1 (9.1%) mutations. Acral/mucosal melanomas exhibited distinct mutation patterns compared to non‐acral melanomas. Tumour mutational burden estimated using ACTOnco was not associated with ICI efficacy. Notably, genetic alterations in the p53 pathway (CDKNA2 loss, MDM2 gain/amplification and TP53 mutation) accounted for 36.4% and were significantly associated with unfavourable PFS (median PFS 2.7 months vs. 3.9 months, P = 0.0394). Moreover, 26 genes were identified as differentially expressed genes that were upregulated in patients with clinical benefits compared to those without benefits. Four genes, GZMH, GZMK, AIM2 and CTLA4, were found to be associated with both PFS and OS. Conclusion Genetic alterations in the p53 pathway may be critical in Asian patients with melanoma undergoing ICI treatment. Further investigation is required to explore this mechanism and validate these findings.